2021
DOI: 10.3389/fpsyg.2021.776833
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sporting and Physical Practice on Visual and Kinesthetic Motor Imagery Vividness: A Comparative Study Between Athletic, Physically Active, and Exempted Adolescents

Abstract: The interest of motor imagery practice on performance and motor learning is well-established. However, the impact of sporting and physical practice on motor imagery vividness is currently unclear, especially in youth. Two-hundred-and-forty adolescents were recruited to form different groups. For each age group (age-group 1, A-G1 with 13years≤age≤14years 6months vs. age-group 2, A-G2 with 14years 6months<age≤16years), 40 athletes, 40 active adolescents, and 40 exempted were recruited (20 girls and 20 boy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Therefore, employing MI techniques may well be beneficial for some autistic people, although an individual approach is likely to be most appropriate. Indeed, MI ability in typical populations is variable ( Moran et al, 2012 ; Cumming and Eaves, 2018 ) and influenced by multiple factors such as sporting and dance experience, MI practice, motor and cognitive ability and tactile discrimination ( Isaac and Marks, 1994 ; Arvinen-Barrow et al, 2007 ; Pelletier et al, 2018 ; Krüger et al, 2020 ; Dhouibi et al, 2021 ; Mao et al, 2022 ). Therefore, future research examining MI ability and impact of MI training on motor coordination in autistic populations will need to take into account individual differences.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, employing MI techniques may well be beneficial for some autistic people, although an individual approach is likely to be most appropriate. Indeed, MI ability in typical populations is variable ( Moran et al, 2012 ; Cumming and Eaves, 2018 ) and influenced by multiple factors such as sporting and dance experience, MI practice, motor and cognitive ability and tactile discrimination ( Isaac and Marks, 1994 ; Arvinen-Barrow et al, 2007 ; Pelletier et al, 2018 ; Krüger et al, 2020 ; Dhouibi et al, 2021 ; Mao et al, 2022 ). Therefore, future research examining MI ability and impact of MI training on motor coordination in autistic populations will need to take into account individual differences.…”
Section: Discussionmentioning
confidence: 99%
“…Further, this paradigm may be more suitable for older children than younger children as the ability to engage in the MCP improves with age. Boys may be more apt than girls to engage in the MCP ( Dhouibi et al, 2021 ). Nonetheless, the ease of measurement and consistent results in children continue to allow researchers to use this paradigm to assess MI ability in children.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Dey et al ( 16 ) show that participation in sports improves mental representation in children, but it is not yet clear which modality (KI, IVI or EVI) was used and contributed the most. Dhouibi et al ( 17 ) found that adolescent athletes use the visual MI more frequently than non-athletes and that this ability is more vivid, pronounced and evoked than KI. The development of KI ability is a gradual process that can take many years to reach completion.…”
Section: Introductionmentioning
confidence: 99%